Concomitant Electrophysiological Study with Transcatheter Aortic Valve Implantation to Predict Risk of Atrioventricular Block - Demuner, Patricia; Freitas, Daniel de Magalhães; Oliveira, Frederico Lopes de; Alessi, Silvio Roberto Borges; Prudente, Maurício Lopes; Fernandes, Fernando Henrique; Barbosa, Flávio Passos; Guimarães, Ellen Gonçalves; Silva, Ricardo Curado de Oliveira e; Gardenghi, Guiulliano (JOURNAL OF CARDIAC ARRHYTHMIAS, 2023)
Introduction: Data on the impact of left bundle-branch block after transcatheter aortic valve implantation (TAVI) are scarce, and treatment has been individualized. Based on this, the electrophysiological study (EPS) concomitant with TAVI may be a strategy for the early stratification of patients needing permanent pacemaker implantation (PPM). Objective: To describe the use of EPS in risk stratification of a definitive pacemaker in patients undergoing TAVI. Materials and methods: Data from seven patients with indications for TAVI due to critical aortic stenosis were retrospectively evaluated. The EPS was performed with a quadripolar diagnostic catheter in His bundle to measure the His-ventricle (HV) interval. Measurement of HV at 70 ms or above was used for discussion on PPM implant indication. Results: Four analyzed patients evolved with left bundle-branch block after TAVI. PPM implantation was indicated for one patient, and the surgery was performed uneventfully during the same hospital stay. Before TAVI, the HV interval ranged from 46 to 58 ms (mean = 53.2 ms), increasing to 52 to 84 ms (mean = 62.8 ms) immediately after valve intervention. Conclusion: The strategy of EPS during TAVI is viable to stratify patients early according to the risk of 2nd or 3rd-degree atrioventricular block, allowing adequate treatment.